Biodiversity assessment of the Lower Mekong Basin: evolutionary novelties in gemmular morphotraits of Genus Corvospongilla (Porifera: Spongillida) with description of a new species from Khorat Plateau, and biogeographic notes - Ruengsawang, Nisit; Sangpradub, Narumon; Cubeddu, Tiziana; Pronzato, Roberto; Manconi, Renata (Zootaxa, 2024)
A new occurrence of the genus Corvospongilla (Porifera: Demospongiae) is recorded from the Southeast Asia freshwater of Khorat Plateau, northeast Thailand. This is the second record of the genus from the Lower Mekong Basin with the discovery the new species Corvospongilla lampaoensis sp. nov. inhabiting a eutrophic lentic habitat (in Lam Pao Reservoir) on manmade structures of fish farming and fishery. Skeleton and gemmules morphotraits, diagnostic for Genus Corvospongilla of the family Spongillidae (Order Spongillida), were examined by Light and Scanning Electron Microscopy differentiating a new species from its twenty congeners known worldwide. In addition, the comparative morpho-analysis highlighted distant sympatric lineages with a notable morphotraits divergence of Corvospongilla lampaoensis sp. nov. vs Corvospongilla siamensis in two western tributaries of the Lower Mekong. The results from this study expand our knowledge of the order Spongillida adaptive radiation in Asia and fill a gap in the geographic range of the genus Corvospongilla in the Oriental-Indomalayan Region.